Strengthening the Prohibitive Illocutionary Function Through Conversation Implicatures of the Main Characters of the Web Series My Lecturer My Husband Season 2 - Bhrata, Pramudya Dhana; Kusumaningsih, Dewi; Wicaksana, Muhlis Fajar; Handayani, Intan Putri Dwi (Faculty of Humanities, Universitas Jenderal Soedirman, 2023)
Conversational implicature is able to strengthen the contradictory illocutionary function. This paper aims to describe information on strengthening the illocutionary function through conversational implicatures by analyzing the language and sentence structure of the main character's utterances. This research use desciptive qualitative approach. The object of this research is implicitly determined through the utterances of the main characters Arya and Inggit who play “My Lecturer My Husband Season 2” taken from webseries media. The data taken was in the form of words and sentences implied in Arya's conversation/dialogue with Inggit. Data collection techniques used free-involved listening (SBLC), notes/transliteration techniques, and content analysis techniques. Method triangulation is used to examine several combinations of methods/techniques in research related to testing the credibility and validity of data. The process of data analysis was carried out by describing all the uses of conversational implicatures in strengthening the speech of contradictory/unusual illocutionary functions. The results of this study indicate that the language variations in the utterances conveyed by the main characters Arya and Inggit in the webseries